Mensurando o resultado fiscal das operaç\~oes de empréstimo do Tesouro ao BNDES: Custo ou ganho líquido esperado para a uni\~ao? - Thiago Rabelo Pereira; Adriano Sim\~oes; André Carvalhal (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– There is a lot of debate about the fiscal impact of the National Treasury loans to BNDES. Given that the interest rates of the loans are mostly indexed to TJLP, there is, in principle, a fiscal cost equal to the difference between TJLP and the market rates of Treasury debt. However, this calculation ignores the tax gains resulting from operations made possible by the Treasury loans, such as: i ) profits of BNDES resulting from these transactions, which return to the National Treasury through dividends, taxes and retained earnings, ii ) short-term tax gains, due to the expansion of economic output and income through the increase of investments made possible by the Treasury loans, and iii ) long-term tax gains resulting from the fact that the economy's productive capacity will be higher in the coming years, enabling further growth without pressing demand inflation, and generating higher tax revenues. Properly calculating the tax costs and gains resulting from the Treasury loans of R 180 billion in 2009 and 2010, we show that, instead of a fiscal cost, there is a net tax gain.
Keywords: H30; H50; H63; 330